Across the Boundaries of Signs and Media: On Transgeneric Qualities of Selected Contemporary Fiction - Lutostański, Bartosz (Zagadnienia Rodzajów Literackich, 2020)
The following article construes the novel as a genre and explores how the innovations of utilizing multiple semiotic resources and media platforms are transforming it these days. With Marisha Pessl’s Night Film (2013) as the primary example I look into the properties of the multimodal and multimedia novel with a view to presenting various ways of transgressing the parameters of the traditional (monomodal and mono-medial) novel. Drawing from L. Elleström’s theory of “modalities of media” I seek to go to the depth of the semiotic and semantic mechanisms of Night Film and argue how the integration of the verbal and the visual renders a new reading experience. Also, on the basis of J.P. Bolter and R. Grusin’s idea of hypermedia I claim that the multiplication of sign systems and media aims at enhancing the ontological illusion.